Flying blind: The experience of online interprofessional facilitation. Issue 4 (July 2013) - Hanna, Elizabeth; Soren, Barbara; Telner, Deanna; MacNeill, Heather; Lowe, Mandy; Reeves, Scott
Abstract : The role of the facilitator is known to be important in fostering productive interprofessional education (IPE) in the face-to-face (F2F) environment. Online learning can help surmount some of the logistical challenges in IPE by bringing together diverse professionals in multiple geographical locations. Best practices in F2F IPE facilitation are beginning to emerge, but there is scant literature examining IPE facilitation online. What little research exists has focused on the asynchronous environment and suggests that the skill sets of online and F2F facilitators have considerable overlap, but there are further demands in the online setting. This qualitative study sought to examine online synchronous IPE facilitation through the self-reported experiences of seven trained facilitators during a 12-week online course. Data collected through focus groups and targeted interviews were analyzed by the research team using constant comparison techniques. Four major themes were revealed: technology as a dynamic force, reduction in non-verbal cues, evolution of the online IPE group process over time and the importance of co-facilitation. The foundations of IPE facilitation were seen to carry over to the online setting. This study has implications for the training of IPE facilitators and for the design of online IPE learning experiences.